Who benefits from big government? A life satisfaction approach - Bodo Knoll; Hans Pitlik (WWWforEurope, 2014)
Which impact does government size have on life satisfaction, and how do effects of bigger government differ between income groups in society? Previous studies typically employed country averages and thus neglect possibly heterogeneous happiness effects between income groups. The paper addresses empirically the effects of government spending on subjective well-being of individuals belonging to different income groups. Our analysis is based on individual data from 25 European countries participating in the European Social Survey. In contrast to most previous studies we take account of the endogeneity between relative income position and reported life satisfaction by an instrumental variable approach. Our results suggest, first, that most government spending categories, including social protection, are on average negatively related to individual well-being. Secondly, estimated marginal effects of health, education and social protection spending at different income levels show that spending increases always have a stronger negative effect on high income groups' well-being than on low income groups' life satisfaction. For all government spending categories, marginal happiness effects of higher public spending are clearly negative for income groups at the top.
Keywords: I31; H40; H11; 330; Life satisfaction; government size; health spending; education spending; social protection; instrumental variables